Automatic strain sensing measurement on steel beam using strain gauge. (2021) - Vijay Anand, L.D.; Hepsiba, D.; Palaniappan, Shanthi; Sumathy, B.; Vijayakumar, P.; Sheeba Rani, S.
Abstract: The metal beams are used in various fields such as industries, construction and vehicle structure. The capacity of load in metal beam depends on the metal and applications. The measurement of strain on the beam is difficult using conventional method. In recent years, strain gauge is used to measure the strain on mild steel beams. It is a sensor whose resistance values are changed with respect to the applied load. The change in resistance is small in magnitude which its effect can be sensed by a wheatstone bridge. It is directly proportional to the applied strain. The different process parameters and its effects are studied through optimization and variance analysis.